2014
DOI: 10.4236/nr.2014.515081
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Oxo-Degradable-Polyethylene and Polylactic Acid Films Embodied in the Substrate of the Edible Fungus <i>Pleurotus ostreatus</i>

Abstract: Degradable plastic mulch is being used to overcome the negative environmental impacts of burning and landfilling agricultural plastic waste. In this study P. ostreatus was used to model the capacity of a vegetal species to degrade conventional and degradable plastic films. Plastics studied were oxo-degradable polyethylene (OXO-PE), UV-irradiated oxo-degradable polyethylene (UV-OXO-PE), polylactic acid (PLA) and conventional polyethylene (C-PE). The cultivation of P. ostreatus resulted in a reduction in the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is composed of an aliphatic-aromatic mixture of the copolyester Ecoflex ® (also produced by BASF) and polylactic acid (PLA). All the plastics were cut into 150 × 10 mm probes, and half of each type of plastic was abiotically oxidized in a previously described weathering chamber built at the university [15], in order to simulate the degradation produced by use, UV radiation and temperature. In the chamber, the materials were exposed to 50˚C, 80% relative humidity and a radiation interval 300 -460 nm during 216 hours, the time needed for the OXOLDPE to decrease its elongation at break to values near to 100%, because of the abiotic degradation process.…”
Section: Tested Materialsmentioning
confidence: 99%
“…It is composed of an aliphatic-aromatic mixture of the copolyester Ecoflex ® (also produced by BASF) and polylactic acid (PLA). All the plastics were cut into 150 × 10 mm probes, and half of each type of plastic was abiotically oxidized in a previously described weathering chamber built at the university [15], in order to simulate the degradation produced by use, UV radiation and temperature. In the chamber, the materials were exposed to 50˚C, 80% relative humidity and a radiation interval 300 -460 nm during 216 hours, the time needed for the OXOLDPE to decrease its elongation at break to values near to 100%, because of the abiotic degradation process.…”
Section: Tested Materialsmentioning
confidence: 99%
“…However, depending of the type of plastic and environmental conditions (humidity, temperature, oxygen concentration, and UV radiation), it is possible that plastics present some evidence of degradation such as discoloration and loss of mechanical properties. Santa Cruz-Navarro et al [30] reported a reduction of elongation at break, an indicator of loss of mechanical properties, of 33%-70% for different types of plastic films embodied in substrates used in cultivation of P. ostreatus.…”
Section: Discussionmentioning
confidence: 99%
“…It is known a series of polyolefin compositions with the addition of naturally occurring biodegradable polymers, such as poly(hydroxyalkanoates) [6,7] or poly(lactic acid) [8,9] required the specific composting conditions. For example, the biodegradability of poly(lactic acid) is fully realized only at an elevated temperature (50-60 • C) [10].…”
Section: Introductionmentioning
confidence: 99%